The Fraternal Birth Order Effect Is Robust and Important. - Bailey, J. Michael (Archives of Sexual Behavior, 2018)
The article presents a commentary to the article ''Fraternal Birth Order, Family Size, and Male Homosexuality.'' The author analyzes the statistical errors in the scientific findings of meta-analysis of fraternal birth order effect (FBOE) on male sexual orientation, such as selective reporting of findings that may have influenced results, replicability, reproducibility and importance of the FBOE.